2006
DOI: 10.1021/ac051972y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Analytical Bias in Metabonomic Studies of Human Blood Serum and Plasma

Abstract: Concurrent with the explosion in the number of publications reporting biomarker discovery by profiling technologies, such as proteomics and pattern recognition, has been the increase in evidence highlighting the susceptibility of these approaches to analytical and experimental bias. The work presented here addresses these timely issues by delivering a detailed characterization of the effect of common sources of bias in clinical studies on serum and plasma profiles generated by a key technology in metabonomics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
187
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 225 publications
(197 citation statements)
references
References 37 publications
8
187
0
2
Order By: Relevance
“…The metabolites assigned from the 1 H NMR spectra are summarized in Table S2. High interpersonal variations have been previously reported not only in the metabolic profiles of urine 16 and plasma 17 , but also in the gut microbial composition 18 and fecal metabolites 11 , implicating that the genetic background and environmental diversity significantly contribute to the metabolic phenotype of the host. Aside from being requested to abstain from alcohol for 24 h prior to fecal sample donation, the donors enrolled in the study were not subjected to any dietary restrictions, which could enhance the interpersonal variations observed.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The metabolites assigned from the 1 H NMR spectra are summarized in Table S2. High interpersonal variations have been previously reported not only in the metabolic profiles of urine 16 and plasma 17 , but also in the gut microbial composition 18 and fecal metabolites 11 , implicating that the genetic background and environmental diversity significantly contribute to the metabolic phenotype of the host. Aside from being requested to abstain from alcohol for 24 h prior to fecal sample donation, the donors enrolled in the study were not subjected to any dietary restrictions, which could enhance the interpersonal variations observed.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To detect reliable molecular biomarkers, it is imperative to handle biological fluids according to standardized procedures and to evaluate the effects of preanalytical parameters on the final result to avoid artifacts (1,2 ). Earlier studies on urine, plasma, and cerebrospinal fluid (CSF) 9 have shown that sample handling can affect the stability of proteins as well as metabolites (3)(4)(5)(6)(7)(8)(9)(10)(11). Standardized sample handling is also important when trying to compare results between different laboratories (12)(13)(14).…”
Section: © 2011 American Association For Clinical Chemistrymentioning
confidence: 99%
“…For functional genomic studies to specifically address the influence of the strain background two papers were chosen that demonstrate the profound influence the genetic background has on the metabolic function and phenotype of a genetically modified organism (Hough et al 2002;Sam et al 2001). Finally a combination of clinical trials and studies of human metabolism where samples have been taken under less strict control of external variables were also considered (Brindle et al 2002;Poston et al 2006;Wolff et al 2004;Siu et al 2006;Townsley et al 2006;Khor et al 2006;Teahan et al 2006). These resultant reporting requirements were then compared with the information captured by other standards initiatives including MIAME (Minimum Information About a Microarray Experiment; Brazma et al 2001;Quackenbush 2004), (minimum information about a genome sequence (MIGS); http://www.genomics.ceh.ac.uk/genomecatalogue; Field et al 2006), CEBS and the human proteome organisation-proteomics standard initiative's (HuPO-PSI; minimum information about a proteomics experiment (MIAPE) ;Taylor 2006;Orchard et al 2003;Orchard et al 2005).…”
Section: The Analytical Process Used To Generate the Reporting Requirmentioning
confidence: 99%